Instrumental and anthropometric studies in physical rehabilitation of patients with rheumatoid arthritis - Nogas, A. (Journal of Education, Health and Sport, 2021)
Rheumatoid arthritis is an autoimmune disease of unknown etiology, characterised by pain, stiffness, and swelling in the joints of the hands and feet, but the disease can also affect other joints. The disease is quite common among rheumatological pathologies and is observed in an average of 1% of the population. A thorough examination of a patient with rheumatoid arthritis, early detection of the main radiological signs of the disease, the level of functional and organic disorders, and the establishment of a rehabilitation diagnosis are essential, which is the basis for building a further personalised physical rehabilitation programme. The purpose of the paper is to determine the severity of the disease in patients with rheumatoid arthritis using instrumental and anthropometric methods of research to form an individual approach to rehabilitation. Materials and methods: the study was conducted on the basis of the Rheumatology Department and the Department of Rehabilitation Treatment with Traditional and Alternative Methods of the Rivne Regional Clinical Hospital named after Yuriy Semenyuk. The study involved 216 patients with rheumatoid arthritis, including 178 women (82%) and 38 men (18%). The patients were aged 25 to 59 years (mean age – 46±0.24). The following research methods were used: questionnaire, history taking, objective examination, instrumental methods of research (radiography), anthropometric methods (Ketle index), statistical methods. Results. Clinical and radiological stage I was diagnosed in 50 (23 %) patients, stage II – in 102 (47 %) patients, and stage III – in 64 patients (30 %). It was found that most patients had radiological stage II with characteristic radiological symptoms (periarticular osteoporosis with minor destruction of the subchondral bone; slight narrowing of the joint gaps, single usurps). Average body mass index values indicate that patients are generally overweight, which is a negative factor in the onset and progression of rheumatoid arthritis. Body mass index is an important indicator in determining the indications for treatment and rehabilitation. Conclusion. As a result of the examination, we found that most patients with rheumatoid arthritis were diagnosed with clinical and radiological stage II. The average BMI values indicate that, in general, patients are overweight, which is a negative factor in the progression of rheumatoid arthritis. The above data give grounds for the development and implementation of the concept of physical rehabilitation of patients with rheumatoid arthritis aimed at reducing clinical symptoms of the disease, reducing body mass index and improving the quality of life of patients.